PERSEPSI MASYARAKAT TERHADAP LAYANAN AGEN46 MITRA PT. BANK NEGARA INDONESIA (PERSERO) TBK DI KABUPATEN MINAHASA UTARA - Koontud, Selly Precillya; Tilaar, Wenny; Pangemanan, Paulus Adrian (Sam Ratulangi University, 2022)
This research was conducted to analyze the public's perception of the services of Agen46 Partner of PT. Bank Negara Indonesia (Persero) tbk in North Minahasa Regency. The analysis used in this research is Likert scale analysis. This type of research is qualitative research. The data used in this study are primary data and secondary data. The population in this study is 46 BNI agents in North Minahasa Regency with a total of 50 agents46. The research sample was 11 BNI 46 agents who were taken by purposive sampling method with 55 respondents who used the services. The research time is for 3 months from February to April 2022. The results show that the index number of public perceptions of the services of agents 46 partners of PT. Bank Negara Indonesia tbk is very good at helping people in the North Minahasa district to reach financial services and more and more community groups in various regions in Indonesia including North Minahasa District are using banking financial services.